Looking for the Workforce - the Elderly, Discouraged Workers, Minorities, and Students in the Baltic Labour Markets - Mihails Hazans (European Regional Science Association (ERSA), 2005)
This paper looks at the evolution of the labour markets in Estonia, Latvia, and Lithuania since the beginning of transition until 2003, with a particular focus on labour force participation. Do the marked differences in labour market policies between the countries result in different patterns of participation? What are the obstacles to and driving forces of participation? We find that relative contribution of participation and demographic trends to the dynamics of the labour force varied substantially both over the years and across the three countries. Participation, in turn, has been shaped by sometimes complicated interaction between educational choices, pension reform, policy changes, and external shocks. Resulting differences in trends and patterns are quite substantial, indicating that there is a room for increasing participation in each of the countries. Panel data analysis of determinants of participation and discouragement suggests that increasing after-tax real minimum wage has significant positive effect on participation and reduces discouragement in Lithuania. In Estonia, by contrast, positive effect of minimum wage on participation is found only for teenagers of both genders and for young males. Members of ethnic minorities, especially females, in all three Baltic countries are less likely to be in the labour force, other things equal.
Keywords: 330